Pengaruh Kompensasi, Kepuasan Kerja, dan Motivasi Kerja Terhadap Loyalitas Karyawan Waroeng Spesial Sambal Kota Yogyakarta - Setiyawan, Rizal Surya; Lysander, Mohammad Ahyar Syafwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to explore the impact of compensation, job satisfaction, and work motivation on employee loyalty. Employee loyalty is crucial for maintaining stability and productivity within an organization, making it important to understand the factors influencing it. This study employs a quantitative approach using a questionnaire consisting of closed- and open-ended questions, utilizing a Likert scale to measure employees' perceptions of compensation, job satisfaction, work motivation, and loyalty. The questionnaire was distributed using a census method, successfully gathering responses from 77 employees. The data analyzed were collected from employees of Waroeng Spesial Sambal who had worked for at least two years and held waiter positions across 18 branches in Yogyakarta. The findings reveal that compensation has a positive and significant impact on employee loyalty, indicating that providing timely, comprehensive, and fair compensation can enhance employee loyalty to the company. Job satisfaction was also found to have a significant positive impact, demonstrating that employees who feel satisfied with their work tend to exhibit higher levels of loyalty. Additionally, work motivation contributes positively to loyalty, suggesting that companies need to formulate specific strategies to enhance employees' intrinsic and extrinsic motivation. Overall, this study concludes that compensation, job satisfaction, and work motivation collectively have a significant positive impact on employee loyalty. These findings can serve as a reference for other researchers interested in employee loyalty issues. Moreover, the results provide valuable information for companies to develop policies focused on improving employee loyalty.